Impulsivity assessed ten years earlier and sociodemographic factors predict adherence to COVID-19 related behavioral restrictions in old individuals with hypertension - Patrizia Steca; Roberta Adorni; Andrea Greco; Francesco Zanatta; Francesco Fattirolli; Cristina Franzelli; Cristina Giannattasio; Marco D'Addario (BMC, 2022)
Abstract Background The COVID-19 pandemic has had clear and dramatic repercussions on health, the economy, and psychosocial well-being. Behavioral measures, such as wearing facemasks and maintaining distance from others, have proven crucial in fighting the contagion's spread. This study aimed to investigate Type A personality traits and sociodemographic predictors of adherence to governmental measures in a sample of frail individuals. Methods A sample of 105 Italians over age 60 (Mean age = 70 years; 60.6% male) affected by hypertension who participated in a previous longitudinal study were assessed through a telephone structured interview. Sociodemographic information and Type A personality traits were retrieved from the original longitudinal study. Adherence behaviors were investigated through several questions regarding the compliance with home confinement, the use of facemasks and the observance of social distancing. Repeated measures Analyses of Variance (RMANOVA), Reliable Change Index, and binomial logistic regression analysis were performed. Results Only 33.3% of the participants reported adherence to all the governmental COVID-19 measures. Being a woman (OR = 4.84; 95% CI = 1.58, 14.90; p < 0.01), being retired (OR = 4.89; 95% CI = 1.09, 21.86; p < 0.05), and suffering from hypertension for a relatively short time (OR = 4.20; 95% CI = 1.22, 14.44; p < 0.05) positively predicted adherence to the governmental measures. Impulsivity resulted in a stable personality characteristic over the last ten years (p = 0.30). Having high levels of impulsivity (OR = 2.28; 95% CI = 1.13, 4.59; p < 0.05) negatively predicted adherence. Conclusions Our results demonstrate that impulsivity is a stable personality facet that can have a robust negative impact on adherence behaviors to health claims. Overall, results show the importance to tailor communication strategies that consider the role of sociodemographic indicators and impulsivity to achieve a high level of adherence.